2018
DOI: 10.1001/jama.2018.17933
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a Program Combining Transitional Care and Long-term Self-management Support on Outcomes of Hospitalized Patients With Chronic Obstructive Pulmonary Disease

Abstract: IMPORTANCE Patients hospitalized for chronic obstructive pulmonary disease (COPD) exacerbations have high rehospitalization rates and reduced quality of life.OBJECTIVE To evaluate a hospital-initiated program that combined transition and long-term self-management support for patients hospitalized due to COPD and their family caregivers. DESIGN, SETTING, AND PARTICIPANTSThis single-site randomized clinical trial was conducted in Baltimore, Maryland, with 240 participants. Participants were patients hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 26 publications
1
65
1
1
Order By: Relevance
“…Where possible, incorporation of a home visit component has clear advantages, especially for the most complex . Some programs follow patients for longer than 30 days postdischarge that helps improve chronic disease management . C‐TraC is a complement to these programs, making high‐quality transitional care available to patients out of the range of home visits or who are in resource‐poor healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where possible, incorporation of a home visit component has clear advantages, especially for the most complex . Some programs follow patients for longer than 30 days postdischarge that helps improve chronic disease management . C‐TraC is a complement to these programs, making high‐quality transitional care available to patients out of the range of home visits or who are in resource‐poor healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,19 Some programs follow patients for longer than 30 days postdischarge that helps improve chronic disease management. 6,19,20 C-TraC is a complement to these programs, making high-quality transitional care available to patients out of the range of home visits or who are in resource-poor healthcare systems. Of note, only 27% of patients in our program required the full follow-up, suggesting the major benefit of the intervention was in the first few weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, our attempts to enroll a broad‐based high‐risk patient population may have limited our ability to provide specialized expertise on specific high‐risk conditions. Programs that focus on one condition, such as chronic pulmonary disease and delirium, have been shown to be effective in reducing readmissions . Thus, for some conditions, condition‐specific programs may be more effective than a program targeted to a broader group of hospitalized high‐risk geriatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Programs that focus on one condition, such as chronic pulmonary disease and delirium, have been shown to be effective in reducing readmissions. 43,44 Thus, for some conditions, condition-specific programs may be more effective than a program targeted to a broader group of hospitalized high-risk geriatric patients. Disease-specific programs may not, however, be optimal in the SNF setting because of the multiple and nonspecific nature of acute changes in condition that result in hospital transfers.…”
Section: Discussionmentioning
confidence: 99%
“…105 In a recent randomized clinical trial, a 3-month program combining transitional care and longterm self-management support not only failed to show a reduction in COPD readmissions at 6 months but showed significantly greater COPD-related hospitalizations and emergency department visits in the intervention group, without an improvement in quality of life. 106 Studies on care bundles to reduce early readmissions have shown the same variability of results. In a randomized controlled trial, Linden and Butterworth did not show any significant reduction in 30-day readmissions with a hospital-based transitional care program.…”
Section: Care Bundlesmentioning
confidence: 96%